2022
DOI: 10.1515/ijld-2022-2067
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing legal translation: a bibliometric study

Abstract: As researches in legal translation advance rapidly, it is critical to keep abreast of emerging trends and critical turns of the collective knowledge development in this field. A bibliometric network using Citespace to examine the original articles obtained from an initial topic search on legal translation can provide a visualized profile for various themes in legal translation, by facilitating the analysis of the status quo, intellectual base, hotspots and emerging trends and providing a systematic review of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…From the literature review, it is reported that the bibliometric analysis of legal translation was conducted in 2022. However, it is noted that the Web of Science -Core Collection database was used (Li, & Hu, 2022). The present study was developed in the Scopus database and it is not stated that no research with similar characteristics to the current one was found.…”
Section: Antecedentsmentioning
confidence: 90%
“…From the literature review, it is reported that the bibliometric analysis of legal translation was conducted in 2022. However, it is noted that the Web of Science -Core Collection database was used (Li, & Hu, 2022). The present study was developed in the Scopus database and it is not stated that no research with similar characteristics to the current one was found.…”
Section: Antecedentsmentioning
confidence: 90%